Long-term outcomes of patients following hospitalization for coronavirus disease 2019: a prospective observational study. (August 2021) - Meije, Yolanda; Duarte-Borges, Alejandra; Sanz, Xavier; Clemente, Mercedes; Ribera, Alba; Ortega, Lucía; González-Pérez, Ruth; Cid, Roser; Pareja, Júlia; Cantero, Irene; Ariño, Miquel; Sagués, Teresa; et al.
Abstract: Objectives: Few data are available regarding follow up of patients with coronavirus disease 2019 (COVID-19) after their discharge. We aim to describe the long-term outcomes of survivors of hospitalization for COVID-19 followed up first at an outpatient facility and subsequently by telephone. Methods: Observational prospective study conducted at a tertiary general hospital. Clinical and radiological progression was assessed and data were recorded on a standardized reporting form. Patients were divided into three groups according to Pao 2 /Fio 2 at hospitalization: Pao 2 /Fio 2 >300, Pao 2 /Fio 2 300–200 and Pao 2 /Fio 2 <200. A logistic multivariate regression model was performed to identify factors associated with persistence of symptoms. Results: For facility follow up, 302 individuals were enrolled. Median follow up was 45 days after discharge; 78% (228/294) of patients had COVID-19-related symptoms (53% asthenia, 56% respiratory symptoms) and 40% (122/302) had residual pulmonary radiographic lesions. Pao 2 /Fio 2 <200 was an independent predictor of persistent dyspnoea (OR 1.87, 95% CI 1.38–2.52, p < 0.0001). Pao 2 /Fio 2 >300 was associated with resolution of chest radiographic lesions (OR 0.56, 95% CI 0.42–0.74, p < 0.0001). Fifty per cent of patients required specific medical follow up after the first consultation and were transferred to another physician . A total of 294 patients were contacted for telephone follow up after a median follow-up time of 7 months. Fifty per cent of patients (147/294) still presented symptoms and 49% (145/294) had psychological disorders. Asthenia was identified in 27% (78/294) and dyspnoea in 10% (28/294) of patients independently of Pao 2 /Fio 2 . Conclusions: Patients with COVID-19 require long-term follow up because of the persistence of symptoms; patients with low Pao 2 /Fio 2 during the acute illness require special attention. Graphical abstract: Image 1